1999
DOI: 10.1128/mcb.19.7.4633
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Product of the Breast Cancer Susceptibility Gene BRCA2 and DSS1, a Protein Functionally Conserved from Yeast to Mammals

Abstract: Germ line mutations in the breast cancer susceptibility gene BRCA2 predispose to early-onset breast cancer, but the function of the nuclear protein encoded by the gene is ill defined. Using the yeast two-hybrid system with fragments of human BRCA2, we identified an interaction with the human DSS1 (deleted in split hand/split foot) gene. Yeast and mammalian two-hybrid assays showed that DSS1 can associate with BRCA2 in the region of amino acids 2472 to 2957 in the C terminus of the protein. Using coimmunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
168
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(178 citation statements)
references
References 45 publications
6
168
0
1
Order By: Relevance
“…Characterization of the endogenous DSS1 protein Previous studies have shown that endogenous human and mouse DSS1 cannot be detected by Western blotting, although both recombinant and yeast DSS1 are detectable by this method (Jantti et al, 1999;Marston et al, 1999;Wei et al, 2003;Gudmundsdottir et al, 2004;Isono et al, 2004;Sone et al, 2004). To detect endogenous human DSS1, we generated an anti-DSS1 antiserum against a full-length DSS1 GST-fusion protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Characterization of the endogenous DSS1 protein Previous studies have shown that endogenous human and mouse DSS1 cannot be detected by Western blotting, although both recombinant and yeast DSS1 are detectable by this method (Jantti et al, 1999;Marston et al, 1999;Wei et al, 2003;Gudmundsdottir et al, 2004;Isono et al, 2004;Sone et al, 2004). To detect endogenous human DSS1, we generated an anti-DSS1 antiserum against a full-length DSS1 GST-fusion protein.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of DSS1 orthologues in Schizosaccharomyces pombe and Saccharomyces cerevisiae leads to reduced growth rate especially at low and high temperatures. Notably, Ddss1 cells exhibit polyploid DNA content at elevated temperatures (Marston et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BRCA2 C-terminus forms a tight complex with a conserved protein, DSS1, and can also interact with Rad51 [19,71,137]. The crystal structure of the BRCA2 C-terminus bound to DSS1 revealed similarity with the heterotrimeric ssDNA-binding complex, RPA, implying a direct interaction of BRCA2/DSS1with ssDNA [138].…”
Section: Molecular Functions Of Brca1 and Brca2mentioning
confidence: 99%